A martensitic stainless steel, preparation method and application thereof
Through the combination of vacuum induction smelting and electroslag remelting, the alloy composition and microstructure of martensite stainless steel are optimized, and the processing difficulty and corrosion resistance of traditional martensite stainless steel are solved, and the effects of high strength, high toughness and good corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411845000.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-16
AI Technical Summary
Traditional martensitic stainless steel has problems in terms of difficult processing, insufficient corrosion resistance, poor high temperature resistance and insufficient quenching hardness, especially the uneven distribution of carbides in high C and high Cr steels, which affects the processing and service life of parts.
The combination of vacuum induction smelting and electroslag remelting is adopted to optimize the alloy composition, including the ratio of C, Si, Mn, Cr, Ni, Mo, V, Ti, Al, and through quenching and tempering treatment, the microstructure is optimized, the grain is refined, and the strength and corrosion resistance of the steel are improved.
It significantly improves the corrosion resistance, wear resistance, hardness and machining properties of martensitic stainless steel, and has evenly distributed carbides, which improves the mechanical properties and corrosion resistance of steel, and is suitable for many fields.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel smelting, and in particular to a martensitic stainless steel, a preparation method and an application thereof. Background Art
[0002] The main purpose of electroslag remelting is to purify metal and obtain clean, uniformly dense steel ingots. It is a smelting method that uses the resistance heat generated when melting slag as a heat source. It is also called electroslag ingot casting and electroslag refining.
[0003] As an important engineering material, martensitic stainless steel has a wide range of applications in many fields. However, in actual use, traditional martensitic stainless steel has exposed some urgent problems, including difficult processing, insufficient corrosion resistance, weak high temperature resistance, and insufficient quenching hardness. Specifically, high-carbon and high-chromium martensitic stainless steel has the characteristics of high hardness, high wear resistance and corrosion resistance, and is widely used in bearings, piston rings and other fields; due to the high C and Cr content in this series of steel, segregation is very easy to occur, and large eutectic carbides are inevitably produced, and the distribution is extremely uneven, which is difficult to eliminate in the subsequent heat treatment process, affecting the processing and service life of parts.
[0004] These defects not only affect the quality and service life of martensitic stainless steel products, but also increase the cost and complexity of the production process. Therefore, developing a new type of martensitic stainless steel to overcome these existing problems has important practical significance and economic value. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a martensitic stainless steel, a preparation method and an application thereof, which solve the problems of insufficient corrosion resistance and machinability of the prior martensitic stainless steel.
[0006] To achieve the above objectives, in a first aspect, the present application provides a martensitic stainless steel, a preparation method and an application thereof, using the following technical solutions:
[0007] A martensitic stainless steel comprises, by weight percentage, the following: C: 0.85%-0.95%, Si: 0.8%-1.2%, Mn: 0.5%-0.8%, Cr: 17%-19%, Ni: 0.3%-0.5%, Mo: 0.9%-1.1%, V: 0.1%-0.3%, Ti: 0.05%-0.15%, Al: 0.02%-0.06%, P≤0.03%, S≤0.03%, and the balance is Fe.
[0008] Preferably, the martensitic stainless steel comprises, by weight percentage, the following: C: 0.9%, Si: 1%, Mn: 0.6%, Cr: 18%, Ni: 0.4%, Mo: 1%, V: 0.2%, Ti: 0.1%, Al: 0.04%, P: 0.02%, S: 0.01% and 77.73% Fe.
[0009] Preferably, the martensitic stainless steel comprises, by weight percentage: C: 0.88%, Si: 0.9%, Mn: 0.7%, Cr: 17.5%, Ni: 0.35%, Mo: 1.05%, V: 0.15%, Ti: 0.08%, Al: 0.03%, P0.01%, S: 0.02%, and 78.3% Fe.
[0010] Preferably, the carbides in the martensitic stainless steel are in the form of particles or short rods, with a size of 3 to 4 μm.
[0011] The present invention provides a method for preparing martensitic stainless steel, comprising the following steps:
[0012] Step 1, smelting process: adopt a smelting method combining vacuum induction melting (VIM) and electroslag remelting (ESR) to obtain a steel ingot; first use a vacuum induction furnace for smelting to obtain a vacuum ingot, the vacuum induction furnace smelting is carried out under argon protection, and then use electroslag remelting to remelt the vacuum ingot; the components of the steel ingot after electroslag remelting include: C: 0.85% ~ 0.95%, Si: 0.8% ~ 1.2%, Mn: 0.5% ~ 0.8%, Cr: 17% ~ 19%, Ni: 0.3% ~ 0.5%, Mo: 0.9% ~ 1.1%, V: 0.1% ~ 0.3%, Ti: 0.05% ~ 0.15%, Al: 0.02% ~ 0.06%, P ≤ 0.03%, S ≤ 0.03%, and the balance is Fe;
[0013] Step 2, forging and rolling process: the steel ingot after electroslag remelting is heated to 1100-1150°C for homogenization treatment, and the heat preservation time is 2-4 hours; during forging, the initial forging temperature is 1050-1100°C, the final forging temperature is not less than 850°C, and the forging ratio is 3-5; the hot rolling start temperature is 1000-1050°C, the final rolling temperature is 800-850°C, and the hot rolling is followed by air cooling to obtain steel;
[0014] Step 3: Heat treatment process: The hot-rolled steel is quenched and tempered, and air-cooled to room temperature to obtain martensitic stainless steel.
[0015] Preferably, during the vacuum induction melting process, the melting temperature, vacuum degree and stirring speed are as follows: the vacuum degree is 1.3×10 - 3Pa, filled with argon to prevent element oxidation, the melting temperature is 1200℃, the stirring speed is 1200~1500r / min, and the melting frequency is 3000~5000Hz.
[0016] Preferably, in electroslag remelting, a vacuum ingot is used as a consumable electrode for electroslag remelting, and the size of the consumable electrode is φ30mm×850mm, and the cooling water flow rate is 850L / h; in the arc starting stage, in order to fully dissolve the refined slag, the smelting current is 1000A. After the refined slag is melted to form a slag pool, the smelting current is constant at 600A, and the magnetic induction intensity is 25 to 50mT.
[0017] Preferably, the refined slag used in the electroslag remelting process has a composition of MgF2:BaO:Al2O3:ZrO2 in a ratio of 5:3:2:0.5. Before remelting, the refined slag is kept at 600°C for 5 hours to remove the internal crystal water.
[0018] Preferably, in the heat treatment process, the quenching treatment includes: heating the hot-rolled steel to 980-1020°C, keeping it at this temperature for 1 hour, and then oil-quenching; the quenched steel is tempered at a tempering temperature of 180-220°C, keeping it at this temperature for 2-3 hours, and repeating this process 5-10 times.
[0019] A martensitic stainless steel having applications in automotive parts production, mold manufacturing, mechanical transmission parts, aerospace parts and medical devices.
[0020] Principle explanation: The technical solution of the present invention has comprehensively improved the performance of martensitic stainless steel through component optimization and process optimization, specifically including the following aspects:
[0021] 1. Silicon is mainly used as an alloying element in martensitic stainless steel and has the following multiple functions:
[0022] Improve the strength, hardness and corrosion resistance of steel: Silicon exists in austenite and ferrite in the form of solid solution, strengthening ferrite and stabilizing the lattice structure of steel, thereby improving the mechanical properties and corrosion resistance of steel;
[0023] Grain refinement: The radius of silicon atoms is different from that of iron atoms. When silicon atoms replace iron atoms and enter the crystal lattice, the lattice constant will change, but it will not significantly affect the macroscopic properties of steel. Instead, it will increase the strength and hardness of steel by increasing the internal stress field of the crystal lattice.
[0024] Optimize phase transformation behavior: Silicon can inhibit the growth of grains during heat treatment, making the grain size smaller and more uniform, and promote the transformation of some unstable austenite to martensite;
[0025] Promote the formation of retained austenite: Through quenching and distribution treatment processes, retained austenite helps to improve the balance of strength and ductility of steel.
[0026] 2. A small amount of nickel plays the following roles in martensitic stainless steel:
[0027] Stabilize austenite: Nickel can expand the austenite zone of iron, making it easier for steel to obtain austenite structure during heat treatment, and then form martensite during cooling, thereby increasing the hardness and strength of the steel; Improve hardenability: Nickel lowers the critical transition temperature and the diffusion rate of each element in the steel, allowing the steel to obtain a more uniform and fine martensite structure after quenching.
[0028] 3. Titanium plays an important role in martensitic stainless steel, specifically:
[0029] Improve strength and wear resistance: Titanium forms stable titanium carbide with carbon, which has high hardness and wear resistance; at the same time, titanium can also form titanium nitride with nitrogen, further improving the wear resistance and corrosion resistance of steel; titanium helps to refine the grains of martensitic stainless steel and improve the strength and toughness of steel; titanium can form a dispersion strengthening phase with carbon, such as TiC, to improve the strength and hardness of steel; titanium can improve the welding performance of martensitic stainless steel and avoid cracks and defects generated during welding.
[0030] 4. Vacuum induction melting and electroslag remelting optimize the performance of steel ingots. Vacuum induction melting: strictly control the melting temperature, vacuum degree and stirring speed, effectively remove impurities and gas elements in the raw materials, and ensure the purity and uniformity of the molten steel;
[0031] Electroslag remelting: further refine the molten steel to make the ingot have a denser structure and uniform component distribution, and reduce inclusions and segregation;
[0032] In summary, the performance of martensitic stainless steel has been significantly improved through component optimization and process improvement.
[0033] The present invention provides a martensitic stainless steel, a preparation method and an application thereof, which have the following beneficial effects:
[0034] The martensitic stainless steel provided by the present invention can improve the performance of the martensitic stainless steel effectively and stably for a long term by optimizing the alloy composition and adjusting the microstructure; including optimizing the corrosion resistance, wear resistance, hardness and machinability of the martensitic stainless steel by adjusting the microstructure; and has the advantages of small and uniform carbide size, excellent mechanical properties, high machinability and good corrosion resistance. These advantages make the stainless steel of the embodiment have broad application prospects in multiple fields, especially in occasions requiring high wear resistance, high strength, high toughness and good corrosion resistance. DETAILED DESCRIPTION
[0035] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0036] The first aspect of the present invention provides a method for preparing martensitic stainless steel, comprising the following steps:
[0037] Step 1, smelting process: adopt a smelting method combining vacuum induction melting (VIM) and electroslag remelting (ESR) to obtain a steel ingot; first use a vacuum induction furnace for smelting to obtain a vacuum ingot, the vacuum induction furnace smelting is carried out under argon protection, and then use electroslag remelting to remelt the vacuum ingot; the components of the steel ingot after electroslag remelting include: C: 0.85% ~ 0.95%, Si: 0.8% ~ 1.2%, Mn: 0.5% ~ 0.8%, Cr: 17% ~ 19%, Ni: 0.3% ~ 0.5%, Mo: 0.9% ~ 1.1%, V: 0.1% ~ 0.3%, Ti: 0.05% ~ 0.15%, Al: 0.02% ~ 0.06%, P ≤ 0.03%, S ≤ 0.03%, and the balance is Fe;
[0038] Step 2, forging and rolling process: the steel ingot after electroslag remelting is heated to 1100-1150°C for homogenization treatment, and the heat preservation time is 2-4 hours; during forging, the initial forging temperature is 1050-1100°C, the final forging temperature is not less than 850°C, and the forging ratio is 3-5; the hot rolling start temperature is 1000-1050°C, the final rolling temperature is 800-850°C, and the hot rolling is followed by air cooling to obtain steel;
[0039] Step 3: Heat treatment process: The hot-rolled steel is quenched and tempered, and air-cooled to room temperature to obtain martensitic stainless steel.
[0040] In one example, the melting temperature, vacuum degree and stirring speed during vacuum induction melting were analyzed. The vacuum degree was 1.3×10 -3 Pa, filled with argon to prevent element oxidation, the melting temperature is 1200℃, the stirring speed is 1200~1500r / min, and the melting frequency is 3000~5000Hz.
[0041] In one of the examples, in electroslag remelting, a vacuum ingot is used as the consumable electrode of electroslag remelting, so that the size of the consumable electrode is φ30mm×850mm, and the cooling water flow rate is 850L / h; in the arc starting stage, in order to fully dissolve the refined slag, the smelting current is 1000A. After the refined slag is melted to form a slag pool, the smelting current is constant at 600A, and the magnetic induction intensity is 25~50mT.
[0042] In one example, the refined slag used in the electroslag remelting process has a composition of MgF2:BaO:Al2O3:ZrO2 with a ratio of 5:3:2:0.5. Before remelting, the refined slag is kept at 600°C for 5 hours to remove the internal crystal water.
[0043] In one example, in the heat treatment process, the quenching treatment includes: heating the hot-rolled steel to 980-1020°C, holding it for 1 hour, and then oil-quenching; by optimizing the quenching process parameters, the material obtains a good martensitic structure and improves the quenching hardness; the quenched steel is tempered at a tempering temperature of 180-220°C and a holding time of 2-3 hours.
[0044] In a second aspect of the present invention, the present invention provides a martensitic stainless steel obtained by the method for preparing the martensitic stainless steel.
[0045] In one example, the martensitic stainless steel includes, by weight percentage: C: 0.85% to 0.95%, Si: 0.8% to 1.2%, Mn: 0.5% to 0.8%, Cr: 17% to 19%, Ni: 0.3% to 0.5%, Mo: 0.9% to 1.1%, V: 0.1% to 0.3%, Ti: 0.05% to 0.15%, Al: 0.02% to 0.06%, P≤0.03%, S≤0.03%, and the balance is Fe.
[0046] In one example, the martensitic stainless steel includes: C: 0.9%, Si: 1%, Mn: 0.6%, Cr: 18%, Ni: 0.4%, Mo: 1%, V: 0.2%, Ti: 0.1%, Al: 0.04%, P: 0.02%, S: 0.01% and 77.73% Fe.
[0047] In one example, the martensitic stainless steel includes: C: 0.88%, Si: 0.9%, Mn: 0.7%, Cr: 17.5%, Ni: 0.35%, Mo: 1.05%, V: 0.15%, Ti: 0.08%, Al: 0.03%, P0.01%, S: 0.02%, and 78.3% Fe.
[0048] In one example, the carbides in the martensitic stainless steel are in the form of particles and short rods with a size of 3 to 4 μm.
[0049] The third aspect of the present invention provides an application of martensitic stainless steel in automobile parts production, mold manufacturing, mechanical transmission parts, aerospace parts and medical equipment.
[0050] In the field of mechanical manufacturing, it is used for manufacturing enterprises' precision parts production, mold manufacturing, and mechanical transmission parts, such as bearings, gears, and shafts, such as automobile engine parts, transmission system parts, and brake system parts; in the field of aerospace, it is used to manufacture engine blades, turbine discs, and landing gear parts; in the field of medical devices, it is used to manufacture medical devices, such as surgical instruments and implants.
[0051] Explanation: Due to the good corrosion resistance and biocompatibility of martensitic stainless steel, the safety and reliability of surgical instruments during use are ensured. At the same time, the high quenching hardness and excellent processing performance effectively guarantee the precision and quality of surgical instruments. Clinical application verification shows that surgical instruments made of martensitic stainless steel provided by the present invention have a longer service life, reducing the risks and pains of patients caused by instrument replacement, and have important social significance and clinical value.
[0052] Example 1 The preparation method of martensitic stainless steel is:
[0053] According to the mass percentage of each element shown in Table 1 Example 1, high-purity metal raw materials with a purity greater than 99.95% were weighed and mixed in a mixer for 3 hours;
[0054] The treated mixed powder is put into vacuum induction melting. During the vacuum induction melting process, the melting temperature, vacuum degree and stirring speed are controlled. The vacuum degree is 1.3×10 -3 Pa, filled with argon to prevent element oxidation, the melting temperature is 1200°C, the stirring speed is 1200r / min, the melting frequency is 300Hz, and a vacuum ingot is obtained;
[0055] The vacuum ingot is remelted by electroslag remelting, and the electroslag remelted steel ingot is heated to 1100°C for homogenization treatment, and the heat preservation time is 2 hours; during forging, the initial forging temperature is 1050°C, the final forging temperature is not less than 850°C, and the forging ratio is 3; the hot rolling start temperature is 1000°C, the final rolling temperature is 800°C, and the hot rolling is air-cooled to obtain the electroslag remelted steel ingot;
[0056] The hot-rolled steel is subjected to quenching and tempering treatments. The hot-rolled steel is heated to 980°C, kept at this temperature for 1 hour, and then oil-quenched. The quenched steel is tempered at 180°C, kept at this temperature for 2 hours, and air-cooled to room temperature to obtain martensitic stainless steel.
[0057] The preparation method of martensitic stainless steel in Example 2 is as follows:
[0058] According to the mass percentage of each element shown in Example 2 of Table 1, high-purity metal raw materials with a purity greater than 99.95% were weighed and mixed in a mixer for 4 hours;
[0059] The treated mixed powder is put into vacuum induction melting. During the vacuum induction melting process, the melting temperature, vacuum degree and stirring speed are controlled. The vacuum degree is 1.3×10 -3 Pa, filled with argon to prevent element oxidation, the melting temperature is 1200℃, the stirring speed is 1350r / min, the melting frequency is 4000Hz, and a vacuum ingot is obtained; the vacuum ingot is remelted by electroslag remelting, and the ingot after electroslag remelting is heated to 1100℃ for homogenization treatment, and the holding time is 3 hours; during forging, the initial forging temperature is 1050℃, the final forging temperature is not less than 850℃, and the forging ratio is 4; the hot rolling start temperature is 1000℃, the final rolling temperature is 850℃, and air cooling is performed after hot rolling to obtain an ingot after electroslag remelting;
[0060] The hot-rolled steel is subjected to quenching and tempering treatments. The hot-rolled steel is heated to 1000°C, kept at this temperature for 1 hour, and then oil-quenched. The quenched steel is tempered at 200°C, kept at this temperature for 3 hours, and air-cooled to room temperature to obtain martensitic stainless steel.
[0061] Example 3: According to the mass percentage of each element shown in Example 3 in Table 1, high-purity metal raw materials with a purity greater than 99.95% are weighed and mixed in a mixer for 4 hours;
[0062] The treated mixed powder is put into vacuum induction melting. During the vacuum induction melting process, the melting temperature, vacuum degree and stirring speed are controlled. The vacuum degree is 1.3×10 -3 Pa, filled with argon to prevent element oxidation, the melting temperature is 1200°C, the stirring speed is 1500r / min, the melting frequency is 5000Hz, and a vacuum ingot is obtained;
[0063] The vacuum ingot is remelted by electroslag remelting, and the electroslag remelted steel ingot is heated to 1150°C for homogenization treatment, and the heat preservation time is 4 hours; during forging, the initial forging temperature is 1100°C, the final forging temperature is not less than 850°C, and the forging ratio is 5; the hot rolling start temperature is 1050°C, the final rolling temperature is 850°C, and the hot rolling is air-cooled to obtain the electroslag remelted steel ingot;
[0064] The hot-rolled steel is subjected to quenching and tempering treatments. The hot-rolled steel is heated to 1020°C, kept at this temperature for 1 hour, and then oil-quenched. The quenched steel is tempered at 220°C, kept at this temperature for 3 hours, and air-cooled to room temperature to obtain martensitic stainless steel.
[0065] Comparative Example 1, using the existing stainless steel formula and combining the heat treatment process of the present invention to obtain Comparative Example 1;
[0066] A smelting method combining vacuum induction melting and electroslag remelting is used to obtain a steel ingot, the chemical composition of which is shown in Table 1; the steel ingot is forged, and during forging, the initial forging temperature is 1050°C, the final forging temperature is not less than 850°C, and the forging ratio is 3; the hot rolling start temperature is 1000°C, the final rolling temperature is 800°C, and after hot rolling, air cooling is performed to obtain a steel ingot after electroslag remelting;
[0067] The hot-rolled steel is subjected to quenching and tempering treatments. The hot-rolled steel is heated to 980°C, kept at this temperature for 1 hour, and then oil-quenched. The quenched steel is tempered at 180°C, kept at this temperature for 2 hours, and air-cooled to room temperature to obtain martensitic stainless steel.
[0068] Comparative Example 2, using the martensitic stainless steel formula provided by the present invention without electroslag remelting to obtain martensitic stainless steel;
[0069] The steel ingot is obtained from a vacuum induction furnace for forging, and the chemical composition of the steel ingot is shown in Table 1; during forging, the initial forging temperature is 1050°C, the final forging temperature is not less than 850°C, and the forging ratio is 3; the hot rolling start temperature is 1000°C, the final rolling temperature is 800°C, and the hot rolling is followed by air cooling to obtain the steel ingot after electroslag remelting;
[0070] The hot-rolled steel is subjected to quenching and tempering treatments. The hot-rolled steel is heated to 980°C, kept at this temperature for 1 hour, and then oil-quenched. The quenched steel is tempered at 180°C, kept at this temperature for 2 hours, and air-cooled to room temperature to obtain martensitic stainless steel.
[0071] By testing the content of the martensitic stainless steel shown in Examples 1-3 and Comparative Examples 1 and 2, Table 1 was obtained;
[0072] Table 1 Chemical composition of martensitic stainless steel in the embodiment and comparative example
[0073]
[0074] Experimental Example 1, used to observe the microstructure appearance of the embodiments and comparative examples;
[0075] Microstructure morphology observation method: After the metallographic samples were ground and polished, they were corroded with a 4% volume fraction of nitric acid alcohol solution. Then, the microstructure morphology of each sample was observed using a metallographic microscope and a field emission scanning electron microscope, and the size and content of carbides in each sample were statistically analyzed.
[0076] The carbides of Comparative Example 1 are distributed in a network shape with a size of 22-26 μm, the carbides of Comparative Example 2 are distributed in a network shape with a size of 8-11 μm, and the carbides in Examples 1-3 are in the form of particles and short rods with a size of 3-4 μm;
[0077] Summary: The martensitic stainless steel samples of Examples 1-3 and Comparative Examples 1 and 2 were processed through the above operations to obtain the size and content parameters of the carbides in each sample in Examples 1-3, wherein the average size of the carbides was 3-4 μm; this indicates that the size of the carbides in the embodiments of the present invention is lower than that in the comparative example, and the dense precipitation and uniform distribution of the carbides after electroslag remelting reduce the cutting wear of the abrasive particles on the martensitic matrix, which can significantly improve the wear resistance of the stainless steel.
[0078] Experimental Example 2 is used to test the mechanical properties of the embodiments and comparative examples; the mechanical properties test includes a hardness test, an impact toughness test, and a cutting efficiency test;
[0079] The impact toughness test method is: the stainless steel of the embodiment and the comparative example is tested using a pendulum impact tester, and the method is as follows: to reduce random errors, the average value of the three values after impact is taken as the impact energy;
[0080] The cutting efficiency test is as follows: using the same cutting machine tool, the cutting tool types are cemented carbide and cubic boron nitride, the stainless steel of the embodiment and the comparative example are subjected to cutting tests, and the tool loss per thousand cuts is recorded; compared with the comparative example, the cutting efficiency of the martensitic stainless steel provided by the embodiment of the present invention can be improved by 20%-30%, the time cost and tool loss cost in the processing process are reduced, and the production efficiency is greatly improved.
[0081] The results of hardness test, impact toughness test and cutting efficiency test were recorded and obtained in Table 2;
[0082] Table 2 Mechanical properties test results
[0083]
[0084] In summary, by analyzing the table, it is found that the martensitic stainless steel provided by the present invention has excellent mechanical properties and cutting performance, is easy to process, and the sample made of the martensitic stainless steel provided by the present invention can achieve a workpiece quenching hardness of HRC58-HRC62.
[0085] Experimental Example 3 is used to test the corrosion resistance of the embodiments and comparative examples;
[0086] The salt spray test is as follows: a salt spray test box is built according to GB10124-88, the stainless steel obtained in the embodiment and the comparative example is placed in the salt spray test box, and the parameters of the salt spray test box are set to ensure the consistency of the test conditions;
[0087] During the test, regularly observe the surface condition of the material or product to be tested and record the corrosion conditions;
[0088] Until the material or product to be tested shows obvious corrosion, the corrosion resistance time is obtained;
[0089] It was recorded that when the corrosion amount reached 1g / m 3 The average corrosion resistance time corresponding to the embodiment is 60h, the corrosion resistance time corresponding to embodiment 1 is 58h, the corrosion resistance time corresponding to embodiment 2 is 60h, and the corrosion resistance time corresponding to embodiment 3 is 62h; the corrosion resistance time corresponding to the comparative example is 24h, and the corrosion resistance time corresponding to comparative example 2 is 32h;
[0090] In summary, the martensitic stainless steel provided in the embodiment of the present invention has good corrosion resistance, and the corrosion resistance time is extended by 50% compared with traditional martensitic stainless steel, which makes the application of the martensitic stainless steel provided by the present invention in corrosive environments such as humidity and ocean more reliable and durable.
[0091] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A martensitic stainless steel, characterized in that: The composition includes carbon, silicon, manganese, chromium, nickel, molybdenum, vanadium, titanium and aluminum, and includes by weight percentage: C: 0.85% to 0.95%, Si: 0.8% to 1.2%, Mn: 0.5% to 0.8%, Cr: 17% to 19%, Ni: 0.3% to 0.5%, Mo: 0.9% to 1.1%, V: 0.1% to 0.3%, Ti: 0.05% to 0.15%, Al: 0.02% to 0.06%, P≤0.03%, S≤0.03%, and the balance is Fe; The carbides in the martensitic stainless steel are in the form of particles and short rods, with a size of 3 to 4 μm; The preparation of the martensitic stainless steel comprises the following steps: Step 1: Melting process: vacuum induction melting combined with electroslag remelting, where the vacuum induction melting temperature is 1200°C and the vacuum degree is 1.3×10 -3 Pa, the stirring speed is 1200-1500r / min, during the electroslag remelting process, the vacuum ingot is used as the consumable electrode, the size is φ30mm×850mm, and the cooling water flow rate is 850L / h; Step 2, forging and rolling process: the steel ingot after electroslag remelting is heated to 1100-1150°C for homogenization treatment, and the heat preservation time is 2-4 hours; during forging, the initial forging temperature is 1050-1100°C, the final forging temperature is not less than 850°C, and the forging ratio is 3-5; the hot rolling start temperature is 1000-1050°C, the final rolling temperature is 800-850°C, and the hot rolling is followed by air cooling to obtain steel; Step 3, heat treatment process: quench and temper the hot-rolled steel, air-cool to room temperature to obtain martensitic stainless steel; heat the hot-rolled steel to 980-1020°C, keep warm for 1 hour, and then oil-quench; temper the quenched steel at a tempering temperature of 180-220°C for 2-3 hours, and repeat 5-10 times.
2. The martensitic stainless steel according to claim 1, characterized in that: By weight percentage, it includes: C: 0.9%, Si: 1%, Mn: 0.6%, Cr: 18%, Ni: 0.4%, Mo: 1%, V: 0.2%, Ti: 0.1%, Al: 0.04%, P: 0.02%, S: 0.01% and 77.73% Fe.
3. The martensitic stainless steel according to claim 1, characterized in that: By weight percentage, it includes: C: 0.88%, Si: 0.9%, Mn: 0.7%, Cr: 17.5%, Ni: 0.35%, Mo: 1.05%, V: 0.15%, Ti: 0.08%, Al: 0.03%, P: 0.01%, S: 0.02%, and 78.3% Fe.
4. The martensitic stainless steel according to claim 1, characterized in that: The preparation of the martensitic stainless steel comprises: A steel ingot is obtained by a smelting method combining vacuum induction melting and electroslag remelting; first, a vacuum induction furnace is used for melting to obtain a vacuum ingot, the vacuum induction furnace melting is carried out under argon protection, and then the vacuum ingot is remelted by electroslag remelting; the steel ingot components after electroslag remelting include: C: 0.85%-0.95%, Si: 0.8%-1.2%, Mn: 0.5%-0.8%, Cr: 17%-19%, Ni: 0.3%-0.5%, Mo: 0.9%-1.1%, V: 0.1%-0.3%, Ti: 0.05%-0.15%, Al: 0.02%-0.06%, P≤0.03%, S≤0.03%, and the balance is Fe.
5. The martensitic stainless steel according to claim 4, characterized in that: In order to fully dissolve the refined slag in the arc starting stage, the smelting current is 1000A. When the refined slag is melted to form a slag pool, the smelting current is constant at 600A, and the magnetic induction intensity is 25 to 50mT.
6. The martensitic stainless steel according to claim 5, characterized in that: The refined slag used in the electroslag remelting process has a composition of MgF2:BaO:Al2O3:ZrO2 with a ratio of 5:3:2:0.
5. Before remelting, the refined slag is kept at 600°C for 5 hours to remove the internal crystal water.
7. Application of the martensitic stainless steel according to any one of claims 1 to 6 in the production of automotive parts, mold manufacturing, mechanical transmission parts, aerospace parts and medical devices, as well as in linear guides and ball screws.
Citation Information
Patent Citations
High-strength martensitic stainless steel and manufacturing process thereof
CN109811252A
Multi-layer composite steel plate for kitchen knife and preparation method of multi-layer composite steel plate
CN114074458A